LEMON BALM (MELISSA OFFICINALIS L.) IS A VALUABLE AROMATIC CULTURE - L. V. Bespalko; E. V. Pinchuk; I. T. Ushakova (Овощи России, 2019)
Spicy-flavoring cultures are an indispensable source of vitamins, macro-and microelements, organic acids. Early and rapid formation and return of the crop greatly increases the value of these crops. One of the valuable spice-aromatic plants of the family Lamiaceae L. is Melissa officinalis (Melicca officinalis L.), which is grown as an essential oil culture. Melissa officinalis contains biologically active substances that can be used to enrich food products. Fresh Melicca officinalis leaves produce essential oil which contains precious substances citronellal, citrategeneric, linalool [1]. Leaves and young shoots in the open ground cut to bloom. Consume fresh or dry melissa demanding soil fertility and irrigation. The article provides information about its origin and biological features. A brief overview of the nutritional and medicinal value is given. One of the important areas of work in the creation of modern vegetable varieties is the selection of high content of biologically active substances with antioxidant activity, and suitability for growing on hydroponic plants in protected soil to supply the population with fragrant vitamin products of fresh herbs all year round. Cv. Zhemchuzhina of Melissa officinalis can be grown in multi circle hydroponics (MCH), using natural substrate (peat mixes). Young shoots of this variety can be consumed as early as 35 days after sowing, in which the content of water-soluble antioxidants in march is 5.9 mg/g in units of Gallic acid. Subsequent cuts should be carried out at intervals of 30-45 days, depending on the season. The article also describes the main elements of the technology of growing medicinal melissa in the open and protected ground for greenery and seed production.